(3JaSjQ MOjKi bhdg Udi Gddg Ydjg hSde (B( (3djS ef GdHQ GdUjGe aj GdSaQ(B)s ((3eOjfI ZQfGWI s)
(3ChdgG (B:s
(3Yf ShGOI Hf CHj GdLYO bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: ( (3fUQ Gddg ef SeY bhdi Ke dh jRO ajg (B) s
(3BNQgG (B:s
(3bdJ PcQfG gPg GdMcGjI HfUgG deG ETJedJ Ydjg ef GdCdaGX GdTGgOI dgPG GdMOjK hTgQI dZJgG hGddg CYde hHg GdKbI hgh MSHfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs